The First Moon Bistatic SAR Imaging Experiment Based on FAST Radio Telescope - Yan Yin; Jinghai Sun; Jitong Duan; Xiaochen Wang; Mingyuan Li; Xinan Yue; Lijia Huang; Peng Jiang; Chibiao Ding (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
This article presents the first bistatic synthetic aperture radar (SAR) Moon imaging experiment based on the five-100-m aperture spherical radio telescope (FAST) and the Sanya incoherent scatter radar (SYISR). We obtain 430 MHz radar images of the Moon surface and the highest resolution of the images reaches 560 m × 630 m. The wide-range and high-resolution images lay a solid foundation for related scientific research. Because FAST lacks the ability to actively transmit signals, SYISR is chosen as the transmitting radar. To mitigate the north–south ambiguity, we alternately image Moon surface areas by controlling the pointing direction of FAST in experiments. The bistatic SAR system brings more system errors compared to the monostatic SAR system. To cope with complex system errors, an error analysis method based on echo characteristics is introduced. The core of this analysis method lies in combining error analysis and compensation with the imaging process, using the imaging results and the changes in echoes to calibrate the errors. This method effectively identifies the source of errors exceeding the range gate and enables FAST to flexibly form a bistatic SAR system with any radar without special hardware modifications. For system errors with less impact, an improved phase gradient autofocus technique is introduced, which can mitigate residual unknown component phase errors in the echo. In addition, in order to image nonephemeris targets based on FAST, such as asteroids, an ephemeris-independent imaging method is introduced and tested with the Moon as the imaging target, which achieved imaging results comparable to that of conventional methods. Finally, mosaic images of Earth-side Moon are obtained. The results validate the reliability of the error analysis method and the imaging technique, as well as the feasibility of FAST imaging the celestial bodies, laying the foundation for FAST to cooperate with other radars to conduct a wider range of deep space targets imaging tasks and scientific exploration.